Jewish Cultural Aspirations (Purdue University Press, 2022)
In the late nineteenth century in Europe and to some extent in the United States, the Jewish upper middle class—particularly the more affluent families—began to enter the cultural spheres of public life, especially in major cities such as Vienna, Berlin, Paris, New York, and London. While many aspects of society were closed to them, theater, the visual arts, music, and art publication were far more inviting, especially if they involved challenging aspects of modernity that might be less attractive to Gentile society. Jews had far less to lose in embracing new forms of expression, and they were very attracted to what was regarded as the universality of cultural expression. Ultimately, these new cultural ideals had an enormous influence on art institutions and artistic manifestations in America and may explain why Jews have been active in the arts in the twentieth and twenty-first centuries to a degree totally out of proportion to their presence in the US population. Jewish cultural activities and aspirations form the focus of the contributions to this volume. Invited authors include senior figures in the field such as Matthew Baigell and Emily Bilski, alongside authors of a younger generation such as Daniel Magilow and Marcie Kaufman. There is also an essay by noted Los Angeles artist and photographer Bill Aron. The guest editor of the volume, Ruth Weisberg, provides an Introduction that places the individual contributions in context.